2008
DOI: 10.1097/bth.0b013e3181590791
|View full text |Cite
|
Sign up to set email alerts
|

Groin Flap Immobilization by Axillary Brachial Plexus Block Anesthesia

Abstract: Pedicled groin flaps are still widely used as soft tissue coverage in hand surgery. Various methods have been described for immobilization of flaps, such as Ace wraps, plaster, and external fixators. The hands of 5 females and 12 males, totaling 17 patients, with severe injury were reconstructed with groin flaps between 2001 and 2005. Patients were operated on under a combination of axillary block and general anesthesia. Motor block effect of axillary anesthesia was used for immobilization of the upper extremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The risk of infarction is close to none as long as the hand and fingers post-debridement is viable with capillary refill times of less than two seconds [ 4 , 5 ]. In other centers, axillary brachial plexus blocks are given combined with general anaesthesia to ensure a secure hand positioning post-operatively [ 6 ] but we demonstrated that is this possible with just WALANT.…”
Section: Introductionmentioning
confidence: 82%
“…The risk of infarction is close to none as long as the hand and fingers post-debridement is viable with capillary refill times of less than two seconds [ 4 , 5 ]. In other centers, axillary brachial plexus blocks are given combined with general anaesthesia to ensure a secure hand positioning post-operatively [ 6 ] but we demonstrated that is this possible with just WALANT.…”
Section: Introductionmentioning
confidence: 82%
“…Harvesting of distant pedicled flaps for bilateral hand reconstruction can be done under brachial plexus and subarachonid block; which avoids complications and costs derived from general anaesthesia, as well as complications of an sudden awakening of the patient, who with his or her movements can shear the recently inset flap [23] .…”
Section: Discussionmentioning
confidence: 99%
“…The next complication with the flap is that the patient has to have the hand in the groin for a prolonged period while it is relatively immobile. This can be performed with techniques such as ace wraps, plaster, external fixators, or under axillary block 21. These techniques are not without their own complications.…”
Section: Discussionmentioning
confidence: 99%